Optimal incentives and securitization of defaultable assets - Malamud, Semyon; Rui, Huaxia; Whinston, Andrew (Journal of Financial Economics, 2013)
We study optimal securitization in the presence of an initial moral hazard. A financial intermediary creates and then sells to outside investors defaultable assets, whose default risk is determined by the unobservable costly effort exerted by the intermediary. We calculate the optimal contract for any given effort level and show the natural emergence of extreme punishment for defaults, under which investors stop paying the intermediary after the first default. With securitization contracts optimally designed, we find securitization improves the intermediary's screening incentives. Furthermore, the equilibrium effort level and the surplus converge to their first best levels with sufficiently many assets.